Manufacture of consumable patterns using additive sheet lamination technology - N. K. Tolochko; P. V. Avramenko; V. B. Kravtsov; A. M. Khartanovich; D. I. Kopchik (Литьë и металлургия)
A comparative analysis of investment casting processes was carried out based on two technological approaches: traditional and modified, based on the use of additive technologies. The advantages and disadvantages of different types of additive technologies used for direct and indirect manufacturing of investment patterns are considered. The features of producing wax and paraffin investment patterns using steel molds manufactured using the additive technology of sheet lamination are experimentally studied. The problems of implementing this technology related to the formation of a stepped relief of the surfaces of the mold cavity are discussed. An effective method for smoothing this relief by removing the recesses of the steps using putty is proposed.